Perbedaan Massa Lemak Antara Pengukuran Skinfold Caliper dengan Bioelectrical Impedance analysis (BIA) pada Atle - Yanti Ernalia; Miftah Azrin; Jessy Latni G (Jurnal Kesehatan Komunitas, 2020)
Research about Skinfold Caliper (SKF) and Bioelectrical Impedance Analysis (BIA) has been frequently studied in athletes. Accurate of SKF is dependent on the technique, skill, and experience of the tester, whereas BIA is less time consuming and easily administered by investigators. The study aimed was to analyze the mean difference of body fat composition (BF%) between SKF and BIA methods among bodybuilders, heavy lifter, and weight lifter athletes. This was an observational analytic research with a cross-sectional design. The data were obtained from direct measurements to 30 athletes (21 men and 9 women). The percentage of body fat data were obtained by SKF and BIA and also anthropometric data (weight and height). The mean of BF percentages was analyzed by multiple paired t-test. The study showed a significant difference in BF% between SKF and BIA methods according to gender, sport, and Body Mass Index (BMI) categories (p<0,05). The mean BF % by skinfold caliper was 18,91 and by BIA was 24,27. Body fat percentage by SKF methods in bodybuilder, heavy lifter, weight lifter, man, woman, normal, overweight, moderates and severe obese wereÂ  12,05; 21,77; 17,67;17,31; 22,67;11,75; 17,83; 23,05; and 34,99. In other, by BIA were 15,34; 28,58; 21,59; 21,99; 29,60; 16,47; 23,69; 29,32; 36,00. It concluded that the mean difference in Body Fat (BF) % between SKF and BIA methods according to gender, kind of sport, and BMI categories was significant (p<0,05), except in severely obese.